Single-vendor multi-buyer game theoretic model under multi-factor dependent demand. (2017) - Guchhait, Rekha; Sarkar, Mitali; Sarkar, Biswajit; Pareek, Sarla
Market demand for any single-type of products depends upon multi-factors. Demand is increasing day-by-day due to the globalisation of products, customer's choice and finally, priorities are now changing according to these factors. In this scenario this paper deals with a single-vendor multiple-buyer supply chain model with imperfect production dependent-demand. This model has been solved by using decentralised and centralised policy and Stackelberg game approach is used to find optimum profit individually in decentralised case. Total profit has been maximised when multi-factor dependent demand is consideredin a single-vendor multi-buyer sustainable supply chain model. Numerical examples and managerial insights are delivered to illustrate the model numerically.